PERHATIAN ORANG TUA TEHADAP KEGIATAN BELAJAR ANAK DI RW 004 KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Fadillah, Nuzul; Ayub, Daeng; Jas, Jasfar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The formulation of the problem in this study is how high is theattention of parents to children's learning activities in RW 004, Tuah Karya Village, Tampan District, Pekanbaru City? How big is the contribution of parents' attention to children's learning activities in RW 004 Tuah Karya Village, Tampan District, Pekanbaru City? The benefits of this study are to find out the high / low attention of parents to children's learning activities in RW 004 Tuah Karya Village, Tampan District, Pekanbaru City, to find a large contribution of parents' attention to children's learning activities in RW 004, Tuah Karya Village, Tampan District, Pekanbaru City. This research is descriptive with a quantitative approach. The population in this study were 70 people. Sampling in this study using simple random sampling. The instrument used was a questionnaire. The parents' attention consisted of 63 statements while the children's learning activities at home consisted of 23 statements. Parents 'attention to children's learning activities in RW 004 in Tuah Karya Village, Tampan Subdistrict, Pekanbaru City was measured by indicators of parents' attention, namely providingchildren's learning facilities, helping children's learning activities, motivating children to learn. While children's learning activities at home are measured by the schedule indicator and implementation, reading and taking notes, repeating learning materials, and doing assignments / homework. Parents' attention to children's learning activities in RW 004 in Tuah Karya Village, Tampan District, Pekanbaru City is high with a mean of 4.38. Based on inferential statistical analysis, the contribution of parents' attention to children's learning activities at home is low, which is 23.80%, which means there are 76.20% determined by other factors that are not part of this study.Key Words: Attention, Parents, Learning Activities, Children, At home